Nancy Clancy : soccer mania - O'Connor, Jane (O'Connor, Jane. Nancy Clancy, 2015)
As her third-grade class makes its selections for the "Graveyard of Boring Words" and learns about "superb synonyms," slow-footed Nancy enthusiastically plays on the soccer team, with the goal of just being mediocre, or maybe even a little better than average.